The Effect of Using ChatGPT Artificial Intelligence (AI) and Digital Literacy on Student Learning Outcomes in Grade XI Civics - Bondar, Cindy K; Ambarita, Prini Desima Evawani; Saragih, Sepriandison (CV Putra Publisher, 2025)
The purpose of this study is to determine the effect of the use of Artificial Intelligence (Ai) Chatgpt and digital literacy on student learning outcomes in the subject of Civics in class XI of SMA Negeri 5 Pematangsiantar in the academic year 2025/2026. The type of research used in this study is quantitative research. Based on the results of the research described above in chapter IV, the following conclusions can be drawn: The effect of the Artificial Intelligence (AI) ChatGPT technology method on student learning outcomes in the subject of Civics in class XI at SMA Negeri 5 Pematangsiantar in the academic year 2024/2025 is